Chemical Composition of the Essential Oil and Petroleum Ether Extract of Korean Pinus densiflora Leaves - Jin Kim, Jong; Chung, Ill-Min; Hye Kim, Eun; Sun Song, Ki; Ahmad, Ateeque (Asian Journal of Chemistry, 2012)
The composition of the leaves of Pinus densiflora essential oil and petroleum ether extract were examined by gas chromatographic-mass spectroscopic analysis (GC-MS). The leaves of P. densiflora on hydrodistillation gave 0.30 % essential oil yield (mL/100 g) of a fresh weight basis. Thirty seven and fourty compounds comprising 96.52 and 99.44 % of the total peak area were identified in the essential oil and petroleum ether extract, respectively. The major components of essentials oils were bicyclo[2.2.1]heptan-2-ol 1,7,7-trimethyl acetate (11.64 %), trans-a-caryophyllene (20.08 %), a-humulene (5.23 %), naphthalene 1,2,4a, 5,6,8a-hexahydro-4,7-dimethyl-1-(1-methylethyl)-(1a, 4aa, 8aa)-(3.89 %), d-cadinene (3.57 %), caryophyllene oxide (7.49 %), t-muurolol (8.57 %), (-)-spathulenol (3.53), t-cadinol (3.30 %), a-cadinol (3.36 %). The major components of petroleum ether extract were acetic acid butyl ester (17.25 %), a-pinene (2.64 %), bicyclo[2.2.1]heptan-2-ol 1,7,7-trimethyl acetate (13.95 %), sabinene (4.48 %), a-selinene (6.18 %), napthalene 1,2,3, 4,4a,5,6,8a-octahydro-7-methyl-4-methylene-1-(1-methylethyl)-(1a, 4aa, 8aa)-(6.77 %), (-)-spathulenol (5.58 %), caryophyllene oxide (8.10 %). The identity of components of essential oil and petroleum ether extract were confirmed on the basis of retention time, mass and supplemented library.